2020
DOI: 10.1016/j.redox.2019.101315
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 5 ameliorates obesity-induced non-alcoholic fatty liver disease through the regulation of oxidative stress and AMP-activated protein kinase signaling

Abstract: Non-alcoholic fatty liver disease (NAFLD) is becoming the most common chronic liver disease globally. NAFLD—which can develop into liver fibrosis, nonalcoholic steatohepatosis, cirrhosis, and hepatocellular carcinoma—is defined as an excess accumulation of fat caused by abnormal lipid metabolism and excessive reactive oxygen species (ROS) generation in hepatocytes. Recently, we reported that Peroxiredoxin 5 (Prx5) plays an essential role in regulating adipogenesis and suggested the need to further investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 50 publications
4
51
0
Order By: Relevance
“…Future studies using these new models, as well as complete knockout mouse models, will help us better understand the physiological roles of PRDXs and provide possible therapeutic targets for drugs against diseases, such as cancer and inflammatory and metabolic diseases. [94,96] High-fat diet Fat, liver…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies using these new models, as well as complete knockout mouse models, will help us better understand the physiological roles of PRDXs and provide possible therapeutic targets for drugs against diseases, such as cancer and inflammatory and metabolic diseases. [94,96] High-fat diet Fat, liver…”
Section: Discussionmentioning
confidence: 99%
“…Prdx5 deficiency leads to increased susceptibility to high-fat-diet-induced obesity, and thus Prdx5-knockout mice fed a high-fat diet show several metabolic abnormalities, including increased body weight, adipocyte hypertrophy, fat accumulation in the liver, hepatic steatosis, and an increased triglyceride level in the serum [94,96].…”
Section: Metabolismmentioning
confidence: 99%
“…In general, lipid metabolism and accumulation in hepatocytes leads to hepatic steatosis, the first step of NAFLD. NAFLD can progress to NASH, advanced hepatic fibrosis, and cirrhosis [39,40]. The present study dealt with the steatosis stage of NAFLD in an animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Another study induced hepatic steatosis in a HepG2 cell line with treatment of FFA to simulate an obese state in vitro . Inducing PrxV overexpression ameliorated hepatic steatosis progression by inhibiting lipogenesis associated protein, SREBP-1 and RAS, and FFA-induced mitochondrial ROS generation ( Kim et al., 2020 ). A follow-up study in mice revealed that the mechanism of PrxV in achieving this role appears to be through phosphorylation of AMPK pathway ( Kim et al., 2020 ).…”
Section: Antioxidants In Ameliorating Obesity and Associated Comorbidmentioning
confidence: 99%
“…Inducing PrxV overexpression ameliorated hepatic steatosis progression by inhibiting lipogenesis associated protein, SREBP-1 and RAS, and FFA-induced mitochondrial ROS generation ( Kim et al., 2020 ). A follow-up study in mice revealed that the mechanism of PrxV in achieving this role appears to be through phosphorylation of AMPK pathway ( Kim et al., 2020 ). Two separate studies have also implicated PrxIV and PrxVI in having a protective role against steatosis by targeting mitochondrial ROS generation ( Yamada and Guo, 2018 ; Lee et al., 2019 ).…”
Section: Antioxidants In Ameliorating Obesity and Associated Comorbidmentioning
confidence: 99%